Ben-Hur (2016): Jesus finds a voice - Kreitzer, L (Bloomsbury Publishing Plc, 2018)
Larry J. Kreitzer There are some films that are so iconic that it is hard to imagine they could ever be remade. William Wyler’s Ben-Hur (1959) is one of those films. The chariot-racing sequence alone is enough to fix the film in the mind of most viewers, even though it takes only eight minutes of the film’s three and a half hours. Wyler’s film was phenomenally successful, and was nominated for twelve Academy Awards, winning eleven of them, a record that has only been matched twice (Titanic in 1997 and The Lord of the Rings: The Return of the King in 2003) . It helped secure the place of Charlton Heston as one of Hollywood’s leading actors, and gifted him with his only Oscar as Best Actor.